Determinants of early sexual initiation among female youth in Ethiopia: a multilevel analysis of 2016 Ethiopian Demographic and Health Survey - Mastewal Arefaynie; Melaku Yalew; Yitayish Damtie; Bereket Kefale (BMC, 2020)
Abstract Background Evidences on determinants of early sexual initiation among female youth is still limited especially; community-level factors are not investigated in Ethiopia. Therefore, the aim of this study was to assess individual and community-level factors associated with early sexual initiation among female youth in Ethiopia. Methods The 2016 Ethiopian Demographic and Health Survey (EDHS) dataset were used and a total of 6143 participants (female youth) were included. Multi-level mixed-effect logistic regression was done to identify individual and community-level factors. Adjusted odds ratio along with 95% confidence interval was used to show the strength and direction of the association. Finally, the level of statistical significance was declared at P value less than 0.05. Results Individual-level factors significantly associated with early sexual initiation among female youth were; age group from 19 to 24 years [AOR = 5.8, 95% CI = (4.6, 7.3)], not attending school [AOR = 14.1, 95% CI = (8.1, 24.7)], ever chewing Chat [AOR = 2.0, 95% CI = (1.3, 3.0)]. From community-level factors: living in Addis Ababa [AOR = 0.3, 95% CI = (0.2, 0.5)], living in Gambella [AOR = 2.7, 95% CI = (1.7, 4.3)] and live in a low proportion of poor communities [AOR = 0.7, 95% CI = (0.5, 0.9)] were significantly associated with early sexual initiation among female youth in Ethiopia. Conclusions Age, low educational status, ever chewing Chat, region and live in a high proportion of poor community had a statistical association with early sexual initiation among female youth in Ethiopia. Improving educational coverage and community-level of wealth status are important intervention areas to delay the age of early sexual initiation.